Post-concussion symptoms and chronic pain after mild traumatic brain injury are modulated by multiple locus effect in the BDNF gene through the expression of antisense: A pilot prospective control study. Issue 1 (1st January 2017) - Khoury, Samar; Segal, Julia; Parisien, Marc; Noreau, Anne; Dion, Patrick; Benavides, Rodrigo; Giguère, Jean-François; Denis, Ronald; Belfer, Inna; Diatchenko, Luda; Rouleau, Guy A.; Lavigne, Gilles J.
ABSTRACT: Background : Mild traumatic brain injury (mTBI) often results in post-concussion symptoms, chronic pain, and sleepiness. Genetic factors are thought to play an important role in poor prognosis. Aims : The aims of this study are to (1) document the prevalence of pain and post-concussion symptoms in mTBI patients in acute and chronic phases (2) determine whether candidate genes predispose to post-concussive symptoms and pain. Methods : Posttraumatic symptoms, evaluated using the Rivermead Post-Concussion Symptoms Questionnaire, and pain were assessed in 94 mTBI patients in the acute phase as well as in 22 healthy controls. Assessment was repeated in 36 patients after one year who agreed to participate in the follow-up visit. Gene polymorphisms and expression were assessed in mTBI patients and healthy controls. Results : In the acute phase, mTBI patients with pain (69%) presented more psychological symptoms and sleepiness and were less able to return to work than those without pain. At one year, 19% of mTBI patients had persistent pain and psychological distress. Two haplotypes (H2 and H3) in the brain-derived neurotrophic factor ( BDNF ) gene were shown to be respectively deleterious and protective against post-concussion symptoms and pain in both acute and chronic phases. Protective haplotype H3 was associated with a decreased expression of the anti-sense of BDNF ( BDNF-AS ). Deleterious haplotype H2 predicted the development of chronic pain at one year, whereas H3 was protective. Conclusions : This pilot study suggests a protective mechanism of a multilocus effect in BDNF, through BDNF-AS, against post-concussion symptoms and pain in the acute phase and possibly chronic pain at one year post-mTBI. The role of antisense RNA should be validated in larger cohorts.